PENGATURAN PENDUDUK PENDATANG DALAM AWIG-AWIG DESA PAKRAMAN - Sudantra, I Ketut (PIRAMIDA; Vol. 4, No. 1 Juli 2008, 2012)
The problems that caused by migrant have been felt nowadays disturbing thecomfort of Balinese community. Because that, many step have been taken, by bothof government and Balinese traditional organization of desa pakraman. Incommon, desa pakraman has been regulated this migrant matter on an adatregulation of awig awig. Even if the models and substances of the migrantregulation are varying, one common principle on awig awig desa pakraman is theprinciple of balance between the rights and obligations of the migrants that liveon domain of desa pakraman.
Keywords: awig awig, desa pakraman, migrants, tamyu